2018
DOI: 10.1051/e3sconf/20184400070
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PM10 high concentration episodes in Warsaw, Krakow and Wroclaw in the years 2005–2017 with application of selected elements of information systems

Abstract: The analysis and comparison of the situations of episodes of high PM10 concentrations in the air in three selected Polish agglomerations: Krakow, Warsaw and Wroclaw in the years 2005-2017 with application of selected elements of information systems (IT) is provided. The role of information systems (technologies) in high pollution episodes in the considered cities is described and the results of measurements performed under the State Environmental Monitoring as well as meteorological data and the dust concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In addition, research conducted in 2016 showed that the highest concentrations of PM 10 in Poland occurred in the agglomeration of Katowice, Rybnicko-jastrzębska and Kraków [29]. Elevated PM 10 concentrations in Krakow have also been identified in earlier years [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research conducted in 2016 showed that the highest concentrations of PM 10 in Poland occurred in the agglomeration of Katowice, Rybnicko-jastrzębska and Kraków [29]. Elevated PM 10 concentrations in Krakow have also been identified in earlier years [30].…”
Section: Discussionmentioning
confidence: 99%
“…Krakow is a city with a long history of air pollution problems and has a significant history in the fight to reduce it. Kobus et al 14 indicated the importance of providing air quality information to cities’ residents to help make them aware of this problem. Danek and Zareba 12 presented similar conclusions on the basis of an analysis of long-term trends and seasonality of PM10 indications in Krakow.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many other studies present long-term trends in changes of air pollutants concentrations in Krakow and their impact on health [74][75][76][77][78][79][80][81][82], the mineralogical composition and microbiological characteristics of aerosols [83,84], the oxidative potential of PM 10 and PM 2.5 [85], the chemical composition of street dust [86] and dry and wet deposition [87][88][89]. The results of measurements from the automatic air quality monitoring station in Krakow were also used to prepare the pollution background necessary in the process of air pollution modeling and the assessment or validation of the dispersion [90][91][92][93][94][95][96][97] or prognostic [98][99][100][101] models used.…”
Section: Introductionmentioning
confidence: 99%